Lithospheric origin of a diamond from the Rio Sorriso area, Mato Grosso State, Brazil - Angellotti, A.; Marras, G.; Morana, M.; Chariton, S.; Stopponi, V.; Medeghini, L.; Romano, C.; Correale, A.; Bindi, L.; Kaminsky, F. V.; Stagno, V. (Frontiers in Geochemistry, 2025)
Diamonds are unique samples that enlarge our vision of the physical and chemical reactions occurring in Earth’s deep, inaccessible mantle. By investigating the minerals and fluids trapped within them, it is possible to ascertain the key conditions relevant to diamond formation, such as pressure, temperature, and oxygen fugacity. In this study, we investigated a diamond from the Rio Sorriso area, Juína (Brazil), a site known for the high abundance of sublithospheric diamonds discovered there. The diamond contained both colorless and greenish optically visible inclusions of Na–Cr-bearing diopside, high-Mg olivine, and enstatite. Thermobarometric estimates of the polished and entrapped inclusions suggest that the diamond likely formed at pressures between 4 and 5 GPa and temperatures of 1,050 °C–1,150  °C. Major and trace elements data from one polished clinopyroxene provide evidence of interaction between the local peridotite and an oxidized Na-rich carbonated melt—a generally proposed growth medium from which diamonds may have crystallized. Our study thus demonstrates that diamonds from underneath the Amazonian craton did not originate solely at lower mantle depths but also within a metasomatized lithospheric mantle.